General Synod of the Church of Ireland: May 2015. (10th December 2015) - Davey, Michael
Abstract : This year's General Synod, the first meeting of the triennium, was held in the now familiar surroundings of the City Hotel, Armagh. Over the past few years there has been a heavy emphasis on finance in the legislative programme, principally with regard to pensions. This year there was one Pensions Bill. It merely formalised the arrangements governing the separate Defined Contributions Schemes that have operated for Northern Ireland and the Republic of Ireland since 2013. The Bill duly passed.